A STUDY OF STRATEGIES FOR SUCCESSFUL HOME WASTE MANAGEMENT - Kumari, Priti (International Journal of Multidisciplinary Research and Studies, 2020)
The problem of managing trash in urban settings is becoming a more complex one as a direct result of the growth in the total quantity of rubbish that is created as a result of human activities. This rise in garbage production is a direct outcome of urbanization. Insufficient waste management in developing nations has had a major negative impact, not only on the natural environment but also on public health (de S. Pereira & Fernandino, 2019). A number of local governments struggle to manage their municipal solid trash in a manner that is environmentally friendly. The major goals of this research were to assess the level of waste management that is practiced in a coastal municipality in India and to investigate the viability of using a particular set of indicators as a way of achieving this objective. A sustainability indicator matrix was used in order to better manage municipal solid trash. This was done for environmental reasons. The Indian National Policy on Solid Waste served as the foundation for the construction of this matrix, which was based on its five defined sustainability features (NPSW).